Experienced poverty stigma is associated with food insecurity, mental health, and resource utilization among Southern US mothers with low income - Rachel A. Liebe; Tuba Khan; Rimsha Azad; Leah M. Adams; Ashlea C. Braun; Heather A. Davis; Sarah A. Misyak (BMC Public Health)
Abstract Background The role of poverty stigma, defined as negative stereotyping based on socioeconomic status, in the relationship between food security and mental health has not been well explored. This study aimed to develop and test a theory to explain the role of internalized and experienced poverty stigma in the relationship between food security and mental health among mothers in the Southern US. Methods A cross-sectional survey was administered in December 2023. The survey was delivered electronically via Qualtrics to mothers living in the southern US who reported a household income below 185% of the federal poverty level. Food security, stigma, and symptoms of anxiety and depression were assessed using previously validated tools. A path analysis was conducted based on the initial conceptual framework and adapted to remove nonsignificant variables. Linear regression was used to assess stigma by resource utilization. Results Mean poverty stigma scores among mothers (n = 1,008) were moderate for internalized (3.1 ± 0.8) and experienced stigma (3.1 ± 1.1). Lower food security was associated with higher internalized (β = 0.10, p < 0.001) and experienced stigma (β = 0.34, p < 0.001). Experienced stigma had a small association with both anxiety and depressive symptoms (β = 0.20, 0.23, p < 0.001). Participation in food pantries (+ 0.17) and the Temporary Assistance for Needy Families (TANF) program (+ 0.45) was associated with higher experienced stigma (p < 0.05). Conclusions Poverty stigma may be a potential area for intervention to address the relationship between food insecurity and mental health among mothers and improve resource utilization.